PENGARUH PEMBIAYAAN MUDHARABAH, MUSYARAKAH, DAN IJARAH TERHADAP PROFITABILITAS PADA BANK BNI SYARIAH INDONESIA PERIODE TAHUN 2014-2017 - Maulana Akhyar; Ridwan Nurdin (JURNAL ILMIAH MAHASISWA EKONOMI ISLAM, 2020)
This research aims to examine and analyze the influence of financing of mudharabah, musyarakah, and ijarah towards profitability in bank BNI Syariah. The research method used is the method of quantitative research. The data used is the data in the financial statements in the form of skunder period 2014-2017 collected from the Bank BNI Syariah website. Method for analysis of data using multiple regression analysis method liniear. The results of this research indicate that financing of mudharabah (X 1), musyarakah (X 2), and ijarah (X 3) either partially or simultaneous effect on profitability (Y) in Bank BNI Syariah in 2014-2017 period in Indonesia.